Titles of architecture research articles in English and Spanish: cross-language genre analysis for disciplinary writing - Perdomo, Bexi; Morales, Oscar Alberto (Penerbit Universiti Kebangsaan Malaysia, 2024)
Research articles titles show lexical, syntactic, and semantic complexity that vary across disciplines and languages. This study analysed architecture English and Spanish Research Articles (RA) titles to identify their main characteristics and to know to what extent they differ between English and Spanish. A genre analysis study was performed following Bhatia's (2002) multi-perspective model. The authors analysed 360 titles in English and Spanish from articles published in six journals indexed in Scopus. Also, architects who were high-ranked researchers were consulted for a better understanding of the practices of the community for RA’s title writing. Results showed similarities (e.g., length) and differences (e.g., title types) across languages. Lexical density was higher in English than in Spanish (t(358) 5.077, p= .000, d= 0.90). Titles tend to be very informative, but the elements informed (e.g., topic or method) and the use of punctuation marks vary across languages (p= .000). The colon (:) emerged as the most commonly used punctuation mark in both languages. It is concluded that architecture RA titles in both languages mostly accomplish the characteristics of a good title proposed in the literature (i.e., introduce the topic, indicate the scope, be self-explanatory, and indicate the nature of the study). These similarities and differences should be included in writing courses for a better understanding of the discursive practices of the Architecture community for RA title writing.